1991
DOI: 10.1063/1.350067
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetic moment and other magnetic properties of epitaxially grown Fe16N2 single-crystal films (invited)

Abstract: Single-crystal Fe16N2 films have been grown epitaxially on Fe(001)/InGaAs(001) and InGaAs(001) substrates by molecular beam epitaxy (MBE). Saturation flux density Bs of Fe16N2 films has been demonstrated to be 2.8–3.0 T at room temperature, which is very close to the value obtained by Kim and Takahashi using polycrystalline evaporated Fe–N films. Temperature dependence of Bs has been measured. Bs changed with temperature reversibly up to 400 °C, while beyond 400 °C, Bs decreased irreversibly. X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(91 citation statements)
references
References 12 publications
8
79
1
Order By: Relevance
“…For example, Sugita et al 3 obtained an in-plane MAE, while Takahashi 18 found a large uniaxial MAE. The only available theoretical calculations of MAE used an empirical tight binding (TB) approximation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sugita et al 3 obtained an in-plane MAE, while Takahashi 18 found a large uniaxial MAE. The only available theoretical calculations of MAE used an empirical tight binding (TB) approximation.…”
Section: Introductionmentioning
confidence: 99%
“…2 This result was not independently confirmed until twenty years later. 3 Owing to the rapid development of the magnetic recording technologies, this confirmation inspired numerous studies of thin-film samples. However, the existence of the "giant" Fe moment remains controversial as many researchers did not reproduce these findings, while others confirmed them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then, 20 years later, that Kim and Takahashi 2 reported polycrystalline, mixed-phase Fe-N films with a saturation magnetization exceeding that of both α-Fe and Co 35 Fe 65 (∼ 2 × 10 6 A/m). However, it took another 20 years for the result to be reproduced (and, in fact, surpassed) by Sugita et al 3,4 Throughout the 1980s and '90s, other measurements of Fe 16 N 2 thin films were reported that generally did not find this large magnetic moment. [5][6][7][8] Concurrently, density-functional theory (DFT) electronic structure calculations were performed, 9-14 finding the moment per Fe ion to be modestly increased with respect to bulk bcc Fe but far short of the 3.5 µ B reported by Sugita et al It was shown 15 that LSDA+U 18 calculations could yield an average moment comparable to that of some experiments (∼ 2.8µ B per Fe), but the parameters (U ≈ 3.94, 1.0, and 1.34 eV on the 4d, 4e, and 8h sites, respectively, with J = U/10) were obtained via an embedded-cluster method with a small screening constant and were not calculated from first principles.…”
Section: Introductionmentioning
confidence: 94%
“…Mössbauer spectroscopy has been performed in many previous works 3,4,8,[38][39][40][41] , and the hyperfine field has been calculated 9,12,13,42 from DFT. Our calculated B hf (found along with our calculated Fe moments in Table I) agrees well with these past results; we find that the Fe sites with N nearest-neighbors exhibit approximately the same field (-23 and -22 T on the 4e and 8h sites), while B hf = −31 T for the 4d sites.…”
Section: A Hyperfine Fieldmentioning
confidence: 99%